Sensory and Instrumental Evaluation of Texture of Cooked and Raw Milled Rices with Similar Starch Properties - Mundo, Angelita M. Del; Kosco, Deborah A.; Juliano, Bienvenido O.; Siscar, Julie Joy H.; Perez, Consuelo M. (Wiley, 1989)
Three pairs of milled rices with similar starch properties (low gelatinization temperature waxy, and low gelatinization temperature low amylose, and intermediate gelatinization temperature intermediate amylose) were assessed for cooked rice properties by two industry taste panels and for raw and cooked rice properties by 30‐member Filipino consumer panels. Only slight differences in texture within pairs were noted by the two industry taste panels who had not been trained to assess boiled raw rice or waxy rice. The Filipino consumer panel gave significantly higher ranked scores for one low‐amylose variety in both raw and cooked forms. Malagkit Sungsong suman sa antala was ranked higher than modern waxy rices. Instrumental methods for translucency and whiteness of raw rice and Instron hardness and stickiness of cooked rice were not able to detect differences perceived by the Filipino consumer panels.